Inhibition kinetics during the oxidation of binary mixtures of phenol with catechol, resorcinol and hydroquinone by phenol acclimated activated sludge - Lobo, Cintia Cecilia (2015)
In this work the aerobic degradation of phenol (PH), catechol (CA), resorcinol (RE), hydroquinone (HY) and the binary mixtures PH+CA, PH+RE, PH+HY by phenol-acclimated activated sludge was studied. Single substrate experiments show a Haldane-type dependence of the respiration rate on PH, RE and HY while the Monod model corresponded to CA. Binary substrate experiments demonstrated that the presence of a second substrate only affected the kinetics, but not the stoichiometry of the oxidation of the tested compounds. While CA inhibited the oxidation of PH, PH inhibited the oxidation of RE and HY. A mathematical model was developed to represent the aerobic biodegradation of the tested phenolic compounds. The agreement between the proposed model and the experimental data indicates that the proposed model can be useful for predicting substrates and dissolved oxygen concentrations in bioreactors treating phenolic wastewaters.